Imbricated structure and hydraulic path induced by strike slip reactivation of a normal fault. (September 2022) - Aubert, Irène; Lamarche, Juliette; Richard, Pascal; Leonide, Philippe
Abstract: In carbonates, fault zones strongly influence local reservoir properties and act as drains or barriers to flows. In the case of reactivated faults, newly developed fracture and fault systems rework and cross-cut pre-existing fault structures. The modifications of initial damage zone and fault core properties alter the fault zone properties and potentially created new fluid pathways. This study of the polyphase Castellas fault zone, developed as normal and later reactivated as strike slip, characterizes the structural pattern related to tectonic reactivation, and estimates the hydraulic behaviour of the fault zone through time. This fault affects carbonates located on La Fare anticlinal (SE France). High resolution mapping, 848 measurements and cross-sections allowed to discriminate the fault structures and the lateral heterogeneity of its architecture. Along the 850m-long studied damage zone we identify 8 principal fault planes, 2 relay zones, 19 secondary fault planes, and fault lenses. The study shows that the fault zone developed as isolated fault segments during the normal activity and acted as a drain to fluid flows during its nucleation. Later strike-slip reactivation led to the main structures visible presently as a well-connected fracture network and un-cemented breccia allowing the fault to be a drain to fluid flows. Highlights: Most of the Castellas fault inner properties are due to the strike-slip reactivation. The overall geometry of Castellas fault zone is dominated by the early extension. Polyphase fault hydraulic properties can change drastically with time and depth. Diagenetic modifications in proto fault zones can create local barriers to flow.